Penerimaan Masyarakat Terhadap Identitas Waria di Kota Jember - Febriyanto Hermawan; Lukman Hakim Alfaridzi (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2025)
Gender identity is part of human existence in society. In Indonesia, the diversity of gender identities other than male and female, such as waria (male and female), often causes social and cultural debates. Waria are a group that are biologically born as men but express themselves as women, both in appearance and behavior. The acceptance of waria in society is not uniform. On the one hand, some people show a tolerant attitude, especially in urban areas that are more open to diversity. On the other hand, negative stigmas against waria are still widely found, which are affected by their limited access to education, work, health services, and public spaces in general. This study uses a qualitative research type. The subjects of this study are waria in Jember City. In this study, researchers use qualitative methods in collecting data by conducting direct observations to obtain data by writing, recording and explaining what is happening to get the right information. In this study, the phenomenological method was also used by searching for data through face-to-face interviews with informants and meeting the agreed informants.